miRNAs as Candidate Biomarker for the Accurate Detection of Atypical Endometrial Hyperplasia/Endometrial Intraepithelial Neoplasia - Giglio, Simona; Annibali, Viviana; Cirombella, Roberto; Faruq, Omar; Volinia, Stefano; De Vitis, Claudia; Pesce, Margherita; Caserta, Donatella; Pettinato, Angela; Fraggetta, Filippo; Vecchione, Andrea (Frontiers in Oncology, 2019)
Endometrial cancer is the most common gynecologic malignancy in developed countries. Estrogen-dependent tumors (type I, endometrioid) account for 80% of cases and non-estrogen-dependent (type II, nonendometrioid) account for the rest. Endometrial cancer type 1 is generally thought to develop via precursor lesions along with the increasing accumulation of molecular genetic changes. Indeed, Endometrial hyperplasia with atypia or Endometrial Intraepithelial Neoplasia (AH/EIN) is the least common type of hyperplasia, but is the type most likely to progress to type 1 cancer, whereas endometrial hyperplasia without atypia (BH) rarely progresses to carcinoma. MicroRNAs are a class of small, non-coding, single-stranded RNAs that negatively regulate gene expression mainly binding to 3’-untranslated region (UTR) of target mRNAs. In the current study we identified a microRNAs signature (miR-205, miR-146a, miR-1260b) able to discriminate between atypical and typical endometrial hyperplasia. The identification of molecular markers that can differentiate between these two distinct pathological conditions is highly considered to be useful for the clinical management of the patients, owing to the fact that hyperplasia with atypical change is associated with a higher risk of develop cancer. A ROC curve analysis showed that each microRNA has a high predictive power in discriminating the two conditions (>90%). With the aim to find a biological role for these three microRNAs we focused our attention on a common putative target involved in endometrial carcinogenesis: the oncosuppressor gene SMAD4. We demonstrated that miR-146a, miR-205 and miR-1260b directly target SMAD4 and induced proliferation and migration of Hec1a cells. These data suggest that impairment microRNAs-mediated of TGF-β pathway, due to inhibition of its effector molecule SMAD4, is a relevant molecular alteration in endometrial carcinoma development. Our findings showed a potential diagnostic role of microRNAs for accurate detection of complex atypical hypeprlasia and improved the understanding of its pivotal role in SMAD4 regulation.